DIGITAL INTEREST DAN TALENT MAPPING DALAM PENINGKATAN MANAJEMEN LAYANAN LEMBAGA DI MTS AL ISLAM JEPARA - Saefudin, Ahmad; Rofiqoh, Naili; Sabilla, Alzena Dona; Laila, Azzah Nur; Candraloka, Olyvia Revalita; Rosyidah, Afifatur; Firmansyah, Andre (Jurnal Abdi Insani, 2025)
The rapid development of technology requires educational institutions to adapt by utilizing digitalization to improve services and learning quality. One urgent need is student interest and talent mapping as well as strengthening institutional branding that is relevant in the digital era. MTs Al Islam Jepara, as a private educational institution, faces challenges in service management and promotion, thus requiring strategic steps through training activities. The purpose of this activity is to enhance teachers’ competence in digital-based talent mapping and to develop effective institutional branding strategies. The method was carried out in three stages: socialization, training, and evaluation. The training included capacity building in student talent mapping and institutional branding with digital promotion strategies. The results show an improvement in teachers’ understanding and skills in identifying students’ interests and talents more systematically, as well as their ability to manage institutional branding strategies through digital media. Participants stated that the program was relevant to the school’s needs, beneficial for improving service quality, and strengthened the institution’s readiness to face modern educational challenges. Evaluation indicated positive responses, with most participants assessing the trainers as competent, materials as easy to understand, and facilities as adequate, although a longer training duration was considered necessary. In conclusion, this community service program successfully improved teachers’ capacity in talent mapping and digital branding, thereby achieving the goal of strengthening educational service management.